(3HQO GdCcHGO Ydi abO GdChdGOs - (3GHf fGUQ GdOjf , eMeO Hf YHO Gddg Hf eMeO Hf CMeO Hf eLGgO, TeS GdOjf CHh HcQ,J (B842 (3g` s
(3ChdgG (B:s
(3CeG HYO agPg JPcQI dChdi GdCdHGH hJSdjI dcd eDef eUGH , JTQM UOQg , hJLdH UHQg hJgOf NWHg , hJNaa CeQg , hfdNU HgG Ydi GdUHQ cJHJgG Ydi GSJYLGd , ai ChGFd ThGd , dZQV GbJVGg GdMGd s
(3BNQgG (B:s
(3ddg ehJ GdeUWai , Efg RQA YXje dG jVGgi GdYXGe , aehJg GdNWH GdLdjd GdPi gGf Hg QRA GdLjGO GdcQGe , dcfg Mi hai QhVI GdhSjdI GdYXei HEYdGA ebGeg , Udi Gddg Ydjg ef aVdI , hSGb JSdjeG Edjg OhGe GdOhGe s
(3Vef eLehY , JQJjHgG (B: (3ef U (B241 - (3U(B279s
(3GfXQ GdLRA GdChd HQbe (B82 (3COHs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B237 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B236s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B110 s
Keywords: (3GdCOHs